PERANAN SEKTOR PERTANIAN DI KABUPATEN MINAHASA TENGGARA - Geraldo G. Pondaag; Gene H.M. Kapantow; Lorraine W.Th. Sondak (AGRI-SOSIOEKONOMI, 2015)
This study aimed to assess the role of the agricultural sector in Southeast Minahasa Regency. The role was measured by the contribution of the agricultural sector in GRDP and the position of the agricultural sector in the regency economy, whether as it was a base or non-base sector. This research was conducted in Southeast Minahasa Regency. The data used were collected from the Central Bureau of Statistics, both South Minahasa and North Sulawesi offices, Planning Board (Bappeda) of Southeast Minahasa, and the Agricultural Agency of Southeast Minahasa Regency. The data were analyzed by calculatingÂ  the contribution of the agricultural sector, LQ and DLQ. The results showed that inspite of the drop in recent years, the agricultural sector remained had the largest contribution in GRDP of Southeast Minahasa Regency. Based on LQ analysis, it was shown that the agricultural sector was one of the four base sectors. Other base sectors were mining and quarrying, manufacturing, and construction sectors. Furthermore, from five sub-sectors within the agricultural sector, two of them were base sub sectors, namely food crops and plantation, while livestocks, forestry and fisheries were non-base sub-sectors. Based on DLQ analysis, the position of the agricultural sector in the future would remain as a base sector. There would be several sub-sectors in agriculture that had the potential to become base sub-sectors in the future, namely food crops, plantation, livestock and forestry, while fisheries sub-sector was predicated to remain as a non base sub-sector in the future.